Reduced susceptibility to triclosan and proposed epidemiological cut-off values for disinfectants and heavy metals in Escherichia coli isolated from Thai tilapia farms: Implications for One Health antimicrobial resistance surveillance - Varangkana Thaotumpitak; Jarukorn Sripradite; Saran Anuntawirun; Nawaphorn Roongrojmongkhon; Woranich Hinthong; Saharuetai Jeamsripong (Veterinary World, 2026)
Background and Aim: Tilapia aquaculture systems may act as reservoirs of antimicrobial resistance (AMR) because continuous exposure to antibiotics, disinfectants, and heavy metals can select for resistant bacterial populations. Although Escherichia coli is widely recognized as an indicator organism for monitoring environmental AMR, information on reduced susceptibility to disinfectants and heavy metals in Southeast Asian aquaculture remains limited. Furthermore, epidemiological cut-off values (ECOFFs) for these agents have not been established for E. coli isolated from Thai tilapia farms. This study aimed to characterize the susceptibility of E. coli isolates to disinfectants and heavy metals, propose ECOFFs, and investigate biofilm formation and resistance determinants to improve understanding of AMR ecology in tilapia aquaculture. Materials and Methods: A total of 333 E. coli isolates recovered from fish (n = 251) and cultivation water (n = 82) were investigated. Minimum inhibitory concentrations for five disinfectants and three heavy metals were determined using the agar dilution method, and ECOFFs were estimated using ECOFF Finder software. Biofilm formation was quantified using the tissue culture plate assay. We detected disinfectant- and heavy metal resistance genes by polymerase chain reaction. Principal component analysis was used to classify isolates according to resistance gene profiles, and multivariable logistic regression was performed to identify factors associated with the presence of the class 1 integron gene (int1). Results: A bimodal minimum inhibitory concentration distribution was observed for triclosan, supporting an ECOFF of 0.004 μg/mL; 52.6% of isolates exceeded this value, indicating a non-wild-type population with reduced susceptibility. In contrast, benzalkonium chloride, chlorhexidine (CHX), glutaraldehyde, and nitrilotriacetic acid exhibited unimodal distributions consistent with wild-type susceptibility. Among heavy metals, isolates were most susceptible to silver nitrate (minimum inhibitory concentration (MIC)₅₀ = 16 μg/mL), whereas higher MIC₅₀ values were observed for copper sulfate (CuSo4) and zinc chloride (ZnCl2). Most isolates (87.7%) exhibited weak biofilm formation, while strong biofilm producers were uncommon and predominantly recovered from cultivation water. Chromosomally encoded efflux pump genes, particularly ydgE (97.9%) and mdfA (92.8%), predominated, whereas plasmid-mediated disinfectant resistance genes were infrequent. Principal component analysis identified four distinct resistance gene clusters, and logistic regression demonstrated significant associations between int1 and several antimicrobial and disinfectant resistance determinants. Conclusion: This study proposes the first ECOFFs for triclosan, selected disinfectants, and heavy metals in E. coli isolated from Thai tilapia farms and demonstrates the emergence of non-wild-type isolates with reduced triclosan susceptibility. The predominance of chromosomally encoded efflux pump genes and the observed resistance gene clustering suggest that intrinsic resistance mechanisms contribute substantially to bacterial persistence in aquaculture environments. These findings provide baseline evidence to support routine disinfectant susceptibility monitoring, prudent biocide use, and the integration of aquaculture into One Health AMR surveillance programs. Keywords: antimicrobial resistance, biofilm formation, disinfectant resistance, Escherichia coli, heavy metals, One Health, tilapia aquaculture, triclosan.